With double trump portfolio through whirls of financial crisis - Rutkauskas, Aleksandras Vytautas; Valiulis, Donatas (Business: Theory and Practice, 2009)
In the article decision management in global currency market FOREX model is presented. The model is based on the adequate for investment profit stochasticity assessment portfolio; earlier suggested by the author; including portfolio and currency exchange rates fluctuations forecasting system; used to evaluate decisions reliability. The possibilities of model practical application are presented. Experimental results of model application enable us to state; that global currency and capital markets are not homogeneous; that is; almost always there are possibilities to find decision management strategy; letting to have advantage over overall market decisions made; using only historical market data. Article in Lithuanian. Su dvigubo kozirio portfeliu per finansų krizės sūkurius Santrauka. Pagrindinis straipsnio tikslas – tolesnis dvigubo kozirio portfelio modelio atitikties tam tikrų globalios valiutų rinkos elgsenos aspektų atspindėjimui vertinimas, efektyvių investavimo strategijų paieška. Šių tikslų siekta nagrinėjant svarbias dvigubo kozirio portfelio analitines savybes ir atliekant statistinį investavimo sprendimų įvertinimą. Eksperimentui buvo pasirinkti FOREX 2007 01 02–2009 04 09 duomenys, tuo siekiama aprėpti svarbius globalius finansų krizės etapus. Reikšminiai žodžiai: dvigubo kozirio portfelis, portfelio investavimo strategija, adekvatusis investicinių sprendimų patikimumo vertinimo portfelis. First Published Online: 10 Dec 2009